Development and evaluation of push pullosmotic pump tablets of valsartan by using ntural polymers - Rozeena Nigar Osman; G. GaneshKumar (International Journal of Pharmacy and Analytical Research, 2022)
Push pull osmotic pump (PPOP) drug delivery system is a dosage form, which provides controlled release of drug for long duration and makes it one of the most promising drug delivery systems in the recent times. The present study was aimed todevelop a POPP for valsartan to achieve zero order release that would reduce thefrequency of dosing and thus improves the patient compliance. The effect of degree of semi permeable coating essentially consisting of Opadry CA and mannitol as pore forming agent also evaluated. In all, 12 batches of valsartan PPOP subjected to various pre and post compression evaluation. The dissolution data was fitted to various mathematical models to describe kinetics of drug release. All the pre and postcompression parameters of formulated PPOP tablets results within the limits. TheFTIR results optimized formulation suggested that good chemical stability of drugand polymer. The optimized formulation (F-10) contain locust bean gum (50 mg)successfully retarded drug release for 12 h and the drug release followed zero orderkinetic with (R2 = 0.974). The accelerated stability profiles indicate that the physicochemical properties of the tablets are not affected on storage at 40 ± 2ºC & 75 ± 5% RH up to 3 months.